High-coercivity magnetically soft alloy and preparation method thereof
By doping C, adsorbing O, and heat-treating the iron-nickel soft magnetic alloy through powder metallurgy, a soft magnetic alloy with high coercivity is prepared, which solves the problem of improving coercivity in the existing technology and achieves high temperature stability. and the dual advantages of low-cost production.
Patent Information
- Application Number
- CN202411594730.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-10
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to effectively improve the coercive force of iron-nickel soft magnetic alloys, especially under the requirement that magnetic performance remains unchanged at high temperatures, and few reports of coercive force increase.
Through the powder metallurgy method, doping C, adsorbing O, and performing heat treatment technology, a high coercive force soft magnetic alloy with a fine matrix γ phase, a flaky FeNi precipitated phase, and appropriate porosity is prepared.
It significantly improves the stubborn power of iron nickel soft magnetic alloys to reach 20 ~ 30A/m, meet the requirements of high temperature stability, and at the same time, the process is simple, the cost is low, and it is suitable for mass production.
Smart Images

Figure CN119361278A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a soft magnetic alloy and a preparation method thereof, in particular to a high coercive force soft magnetic alloy and a preparation method thereof, belonging to the field of soft magnetic materials. Background Art
[0002] Soft magnetic materials are materials whose magnetization occurs when the coercive force is no greater than 1000 A / m. As key materials in power electronics and power conversion equipment, soft magnetic materials possess excellent magnetic properties. They can reach a saturated magnetization state under the influence of an external magnetic field and quickly lose their magnetism after the external field is removed, enabling them to transform and transmit electrical energy.
[0003] Iron-nickel soft magnetic alloys are a type of soft magnetic material with excellent overall magnetic properties and are one of the most representative alloys among soft magnetic materials. These materials are known for their high permeability and low coercivity in weak magnetic fields. By adjusting the alloying element ratio and using appropriate processing techniques, magnetic properties can be controlled to produce soft magnetic materials with high permeability, constant permeability, and moment magnetism. They also have high plasticity and are sensitive to stress, making them suitable for use in pulse transformer materials and inductor cores.
[0004] With the development of industry, higher requirements are placed on the performance of iron-nickel soft magnetic alloys used as core materials for transformers and inductor cores. For example, transformers need to be used at high temperatures (100~200℃), and it is hoped that their magnetic properties such as remanence and magnetic permeability remain basically unchanged. In other words, it is hoped that iron-nickel soft magnetic alloys with high-temperature stability can be developed. The current main method is to increase the coercive force of soft magnetic alloys.
[0005] Coercive force refers to the fact that after a magnetic material is saturated magnetized, its magnetic induction intensity B does not return to zero when the external magnetic field returns to zero. Only when a magnetic field of a certain magnitude is added in the opposite direction of the original magnetizing field can the magnetic induction intensity return to zero. This magnetic field is called coercive force. The greater the coercive force, the stronger the magnet's ability to resist demagnetization. Therefore, improving the coercive force of magnetic materials can eliminate or reduce the loss of their magnetic properties at higher temperatures. At present, there are few reports on improving the coercive force of soft magnetic alloys, and most of the research focuses on improving the coercive force of hard magnetic materials. Jiangsu Zhixing Technology Co., Ltd. discloses a magnetic powder core with permanent magnetic properties prepared by doping Nd, Si, Tb, and Dy in FeNbB magnets, and improving the coercive force of the magnet by Tb and Dy. By using a low-temperature, brittle phenolic resin, ball-milling it to a fine particle size, and uniformly mixing it with a nanoscale composite powder, the melted composite powder is evenly dispersed and fused before being molded into a magnetic powder core. This ensures uniform dispersion of all components, balances interparticle gaps, enhances stability, improves magnetic permeability, and reduces magnetic losses, effectively improving the various properties of the magnetic powder core (Application No.: 2021109778920). However, the preparation process requires a relatively high amount of heavy rare earth elements, Tb and Dy, resulting in high production costs and unfavorable mass production. The coercivity of soft magnetic materials is more significantly influenced by the material's microstructure, such as grain size, phase composition, impurities, and defects. The chemical composition and processing of the material, in turn, determine its microstructure. To date, no studies have examined the influence of the microstructure of soft magnetic alloys on coercivity. Summary of the Invention
[0006] In order to improve the coercivity of the material by controlling the microstructure of the iron-nickel soft magnetic alloy, the present invention provides a high-coercivity soft magnetic alloy and a preparation method thereof. Based on a powder metallurgy method, C doping, O adsorption and heat treatment technology are adopted to prepare a high-coercivity soft magnetic alloy with a fine matrix γ phase, a flaky FeNi precipitate phase and an appropriate porosity.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a high coercive force soft magnetic alloy, characterized in that the chemical composition of the soft magnetic alloy is Fe-xNi-yC-zO and inevitable impurity elements, x is 40-60wt.%, y is 0.05-0.2wt.%, and z is 0.1-0.3wt.%; The microstructure of the soft magnetic alloy includes a matrix γ phase and a FeNi precipitation phase; The average grain size of the γ phase is 20-30 μm; The FeNi precipitated phase is in the form of a sheet, with a length of 20-40 nm and a width of 5-15 nm, and is distributed inside the matrix γ phase; The relative density of the soft magnetic alloy is 96% to 98%.
[0008] As a preferred embodiment, the present invention provides a high coercive force soft magnetic alloy, characterized in that the impurity elements include at least one of P, S, Si and Mn in terms of mass percentage, the P content is ≤0.03wt.%, the S content is ≤0.03wt.%, the Si content is ≤0.04wt.% and the Mn content is ≤0.05wt.%, and the total amount of the impurity elements is ≤0.15wt.%.
[0009] The present invention provides a method for preparing a high coercive force soft magnetic alloy, characterized by comprising the following steps: subjecting alloy powder to pretreatment, forming, sintering and heat treatment in sequence to obtain a product; The pretreatment process is as follows: in an air environment, heating the temperature to 200-300°C at a heating rate of 2-5°C / min, keeping the temperature for 1-2 hours, cooling the furnace to room temperature and then taking the furnace out; The heat treatment process is as follows: in a vacuum environment with a vacuum degree of ≤0.01Pa, heating to 500-600°C at a heating rate of 5-10°C / min, keeping the temperature for 1-2 hours, then cooling to room temperature in water or quenching oil and taking out of the furnace.
[0010] As a preferred embodiment, the present invention provides a method for preparing a high coercive force soft magnetic alloy, characterized in that the alloy powder is prepared by one of gas atomization, water atomization and water-gas combined atomization methods.
[0011] As a preferred embodiment, the present invention provides a method for preparing a high coercive force soft magnetic alloy, characterized in that the average particle size of the alloy powder is 2-5 μm.
[0012] As a preferred embodiment, the present invention provides a method for preparing a high coercive force soft magnetic alloy, characterized in that: the forming is any one of compression molding and cold isostatic pressing; the forming pressure of the compression molding is 100~300MPa, and the holding time is 5~10min; the forming pressure of the cold isostatic pressing is 100~200MPa, and the holding time is 3~8min.
[0013] As a preferred embodiment, the present invention provides a method for preparing a high coercive force soft magnetic alloy, characterized in that the sintering process is: in a vacuum environment with a vacuum degree of ≤0.01Pa, heating to 1200~1300℃ at a heating rate of 5~10℃ / min, keeping warm for 1~4h, cooling to room temperature and taking out of the furnace.
[0014] The invention provides a high-coercive force soft magnetic alloy and a preparation method thereof, characterized in that the coercive force of the soft magnetic alloy is 20-30 A / m.
[0015] Principles and advantages The present invention has made a breakthrough in the preparation technology of high-coercivity soft magnetic alloys, and adopts the synergistic effect of C doping, O adsorption and heat treatment technology to prepare a high-coercivity iron-nickel alloy microstructure.
[0016] Coercivity characterizes a magnetic material's ability to resist external reverse magnetic fields or other demagnetizing effects. Coercivity is a crucial parameter in magnetic circuit design and is closely related to the material's microstructure. The following analysis examines the relationship between chemical composition, grain size, secondary phases, and porosity, and explores how to achieve an ideal microstructure through process optimization.
[0017] The relationship between chemical composition and coercivity. The chemical composition of an alloy is the basis of material properties, and the coercivity of a soft magnetic alloy is affected by its chemical composition. Traditional iron-nickel-based soft magnetic alloys have a Ni content of 30-60 wt.%, and their coercivity is usually around 5 A / m. Alloying is the main method for material modification. Therefore, improving the chemical composition in iron-nickel soft magnetic alloys is one of the methods to increase coercivity. C and O are inevitable impurity elements in the powder metallurgy preparation process. The inventors have found that when the C and O contents are controlled within a certain range, they will exist in the soft magnetic material in the form of solid solution, which is very helpful in increasing the coercivity. The matrix of sintered iron-nickel alloy is γ phase, which is a face-centered cubic structure. The size of its octahedral gap is 0.05 nm. The radii of C and O atoms are approximately 0.077 nm and 0.06 nm, respectively. Therefore, when C and O atoms enter the gaps in the iron-nickel alloy, they will cause a certain amount of lattice distortion. The distortion caused by lattice expansion will lead to the emergence of distortion internal stress. The total stress caused by lattice distortion in a magnetic domain increases, while the wavelength of the equivalent stress wave remains unchanged. The maximum equivalent stress of the equivalent stress wave increases, and the corresponding domain wall energy peak increases, so the coercive force increases. However, when the C and O content is too high, they will appear in the iron-nickel alloy as carbides or oxides, mainly consuming the Fe element in the matrix and will not cause the increase of the domain wall energy peak, so the coercive force decreases. The present invention obtains Fe-Ni-C pre-alloyed powder by adding 0.05~0.2wt.% of graphite during the atomization powder making process, and performs oxygen absorption pretreatment on the pre-alloyed powder, and keeps it at 200~300℃ in an air environment for 1~2h, so that the pre-alloyed powder absorbs 0.1~0.3wt.% of O, thereby modifying the composition of the iron-nickel alloy, obtaining a new Fe-Ni-CO system, and achieving an improvement in coercive force.
[0018] The relationship between grain size and coercive force. The grain boundary is the interface between crystals with the same structure but different orientations. The atomic arrangement at the crystal interface transitions from one orientation to another, so the atomic arrangement at the grain boundary is in a transitional state. The grain boundary is the interface between grains. Since the atomic arrangement orientations of the two grains on both sides of the grain boundary are somewhat different, both try to make the atomic arrangement on the grain boundary conform to their own orientation. When equilibrium is reached, the atoms on the grain boundary form a certain transitional arrangement, and the atomic arrangement on the grain boundary is chaotic, causing it to be in a stress distortion state, thereby inducing micro-stress. Assuming that there is a domain wall at the farthest point where the grain boundary induces stress, then only the grain boundary stress that affects the displacement of the domain wall is considered. Therefore, the coercive force of the domain wall close to the grain boundary will increase. As the grain size decreases, the number of grain boundaries increases, and the coercive force of the magnet increases. In the process of technological development, gas atomization, water atomization, and water-gas combined atomization methods are used to obtain finer-grained powders with an average particle size of 2~5μm. Figure 1 As shown. Due to its high activity, measures such as reducing the sintering temperature and shortening the holding time can be taken to avoid grain growth. Under the above process parameters, a matrix γ phase with fine and uniform grains can be obtained, with an average grain size of 20~30μm, as shown Figure 2 As shown, it is beneficial to improve the coercivity of soft magnetic materials. The grain size measurement method refers to "GB / T 6394-2017 Metal Average Grain Size Determination Method".
[0019] The relationship between the second phase particles and the coercive force. The saturation magnetic induction intensity is a non-structural sensitive quantity, which only depends on the chemical composition and density of the material. The coercive force of the soft magnetic alloy is not only related to the chemical composition and grain size of the material, but also affected by the phase composition. The sintered iron-nickel soft magnetic alloy consists of a matrix γ phase and a small amount of pores. The heat treatment process is the main method to construct a new phase. In the process of technological development, the inventors conducted vacuum heat treatment on the sintered iron-nickel alloy and accidentally found that after the insulation was completed, when the sample was placed in water or oil as a cooling medium for cooling, nanometer-scale second phase particles FeNi could be dispersed and precipitated from the matrix. It is in the form of flakes, with a length of 20~40nm and a width of 5~15nm. Figure 3 As shown in Figure 2, the magnetic domain lines can bend around the second phase particles, increasing the lattice distortion energy, which increases the resistance to the movement of the magnetic domains, thereby pinning the magnetic domains and hindering the migration of the magnetic domains, greatly improving the coercivity of the soft magnetic material.
[0020] The relationship between porosity and coercivity. Generally speaking, powder metallurgy products inevitably have a certain amount of pores. The pores inside the magnet are the centers of stress concentration of the magnet. The more pores a magnet has, the lower its density, the more areas of stress concentration there are, the greater the resistance to the magnetic domains, and the greater the coercivity. The inventors adjusted the porosity to an appropriate amount by controlling the sintering process, which helps to increase the resistance to the magnetic domains and improve the coercivity of the magnet. However, too many pores will affect other properties of the magnet. Therefore, through a large number of experiments, the porosity was finally determined to be 2~4%, which can ensure sufficient coercivity without affecting other properties of the soft magnetic alloy.
[0021] Compared with the prior art, the advantages of the present invention are as follows: 1) Excellent performance. The coercivity is more than three times that of conventional iron-nickel soft magnetic alloys; 2) Simple process. Pure powder metallurgy process, easy for mass production; 3) Low cost. No expensive elements added, no raw material costs, no complicated process, and low process cost.
[0022] In summary, the present invention is based on a powder metallurgy method and adopts the synergistic effect of doping C, adsorbing O and heat treatment technology to prepare an iron-nickel alloy microstructure with a fine matrix γ phase, a flaky FeNi precipitated phase, and an appropriate porosity that is beneficial to improving the coercive force, greatly improving its high-temperature stability, and having the advantages of simple process, low cost, and easy mass production. It can well meet commercial needs and is very suitable for the preparation of soft magnetic alloy products. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope photo of iron-nickel soft magnetic alloy powder.
[0024] Figure 2 This is a metallographic photograph of iron-nickel soft magnetic alloy.
[0025] Figure 3 This is a transmission electron microscope photograph of the FeNi precipitation phase. DETAILED DESCRIPTION
[0026] The method of the present invention is further illustrated below with reference to three examples. Example 1
[0027] A high coercivity soft magnetic alloy and a preparation method thereof, wherein the process is as follows: A. Powder preparation: Prepare the ingredients according to the chemical composition of Fe-45wt.%Ni, add 0.15wt.% graphite powder, and use the water-gas combined atomization method to make the powder. The average particle size of the powder is 3μm, and the total amount of impurity elements is 0.1wt.%; B. Pretreatment: The powder was heated to 300°C at a heating rate of 5°C / min in air, kept at this temperature for 1 hour, and then cooled to room temperature before being taken out of the furnace. C. Forming: After pretreatment, the powder is placed in a mold and pressed into shape. A forming pressure of 200 MPa is maintained for 6 minutes to obtain a blank. D. Sintering: Place the blank into a vacuum sintering furnace, and heat it to 1250℃ at a heating rate of 5℃ / min under a vacuum environment of 0.01Pa or less, and keep it at that temperature for 2h. Then cool it to room temperature and take it out of the furnace. E. Heat treatment: Place the sintered blank into a heat treatment furnace, and heat it to 500°C at a heating rate of 10°C / min under a vacuum environment of ≤0.01Pa, and keep it at that temperature for 2h. Then, place it in water to cool to room temperature and take it out of the furnace; F. Performance test: The coercive force of the iron-nickel soft magnetic alloy is 25A / m. Example 2
[0028] A high coercivity soft magnetic alloy and a preparation method thereof, wherein the process is as follows: A. Powder preparation: The ingredients are prepared according to the chemical composition of Fe-50wt.%Ni, and 0.18wt.% graphite powder is added thereto. The powder is made into powder by water atomization method. The average particle size of the powder is 2.6μm, and the total amount of impurity elements is 0.15wt.%; B. Pretreatment: The powder is heated to 250°C at a heating rate of 5°C / min in air, kept at this temperature for 2 hours, and then cooled to room temperature before being taken out of the furnace; C. Forming: After pretreatment, the powder is placed in a mold and pressed into shape. A forming pressure of 250 MPa is maintained for 5 minutes to obtain a blank. D. Sintering: Place the blank into a vacuum sintering furnace, and heat it to 1300℃ at a heating rate of 5℃ / min under a vacuum environment of 0.01Pa or less, and keep it at that temperature for 1h. Then cool it to room temperature and take it out of the furnace. E. Heat treatment: Place the sintered blank into a heat treatment furnace, and heat it to 600°C at a heating rate of 10°C / min under a vacuum environment of ≤0.01Pa, and keep it at that temperature for 1 hour. Then, place it in water to cool to room temperature and take it out of the furnace; F. Performance test: The coercive force of the iron-nickel soft magnetic alloy is 24A / m. Example 3
[0029] A high coercivity soft magnetic alloy and a preparation method thereof, wherein the process is as follows: A. Powder preparation: Prepare the ingredients according to the chemical composition of Fe-55wt.%Ni, add 0.2wt.% graphite powder, and use the gas atomization method to make the powder. The average particle size of the powder is 3.5μm, and the total amount of impurity elements is 0.15wt.%; B. Pretreatment: The powder is heated to 250°C at a heating rate of 5°C / min in air, kept at this temperature for 2 hours, and then cooled to room temperature before being taken out of the furnace; C. Forming: After pretreatment, the powder is placed in the bag of a cold isostatic press and cold isostatically pressed. A forming pressure of 200 MPa is used and the pressure is maintained for 4 minutes to obtain a blank. D. Sintering: Place the blank into a vacuum sintering furnace, and heat it to 1300℃ at a heating rate of 5℃ / min under a vacuum environment of 0.01Pa or less, and keep it at that temperature for 1h. Then cool it to room temperature and take it out of the furnace. E. Heat treatment: Place the sintered blank into a heat treatment furnace, and heat it to 600°C at a heating rate of 10°C / min under a vacuum environment of ≤0.01Pa, and keep it at that temperature for 1 hour. Then, cool it in oil to room temperature and take it out of the furnace. F. Performance test: The coercive force of the iron-nickel soft magnetic alloy is 30A / m.
[0030] Comparative Example 1-1: The only difference from Example 3 is that no graphite powder is added during the powder making process, and the coercive force of the iron-nickel soft magnetic alloy is only 8 A / m.
[0031] Comparative Example 1-2 The only difference from Example 3 is that 0.4 wt.% of graphite powder is added during the powder making process, more carbides appear, and the coercive force of the iron-nickel soft magnetic alloy is only 9 A / m.
[0032] Comparative Example 2-1 The only difference from Example 3 is that no powder pretreatment is performed, and the coercive force of the iron-nickel soft magnetic alloy is only 10 A / m.
[0033] Comparative Example 2-2 The only difference from Example 3 is that the temperature of the powder pretreatment is 500° C., excessive oxides appear, and the coercive force of the iron-nickel soft magnetic alloy is only 11 A / m.
[0034] Comparative Example 3-1: The only difference from Example 3 is that the sintering temperature is 1000° C., which results in excessive pores and affects the basic strength of the magnet.
[0035] Comparative Example 3-2: The only difference from Example 3 is that the sintering temperature is 1400° C., the grains are too large, and the coercive force of the iron-nickel soft magnetic alloy is only 13 A / m.
[0036] Comparative Example 4-1: The only difference from Example 3 is that no heat treatment was performed, no precipitated phase was present, and the coercive force of the iron-nickel soft magnetic alloy was only 10 A / m.
[0037] Comparative Example 4-2: The only difference from Example 3 is that after the heat treatment, the alloy is cooled in the furnace and no precipitated phase is formed. The coercive force of the iron-nickel soft magnetic alloy is only 12 A / m.
[0038] The above-mentioned examples are only preferred implementation methods of the present invention, and therefore cannot be used to limit the scope of implementation of the present invention. Other equivalent changes, modifications, substitutions and combinations made in accordance with the principles and contents of the present invention still fall within the scope of protection of the present invention.
Claims
1. A high coercivity soft magnetic alloy, characterized in that: The chemical composition of the soft magnetic alloy is Fe-xNi-yC-zO and inevitable impurity elements, x is 40-60wt.%, y is 0.05-0.2wt.%, and z is 0.1-0.3wt.%; The microstructure of the soft magnetic alloy includes a matrix γ phase and a FeNi precipitation phase; The average grain size of the γ phase is 20-30 μm; The FeNi precipitated phase is in the form of a sheet, with a length of 20-40 nm and a width of 5-15 nm, and is distributed inside the matrix γ phase; The relative density of the soft magnetic alloy is 96% to 98%.
2. A high coercivity soft magnetic alloy according to claim 1, characterized in that: The impurity elements include at least one of P, S, Si and Mn in mass percentage, with P content ≤0.03wt.%, S content ≤0.03wt.%, Si content ≤0.04wt.% and Mn content ≤0.05wt.%, and the total amount of the impurity elements ≤0.15wt.%.
3. The method for preparing a high coercive force soft magnetic alloy according to claim 1 or 2, characterized in that: The following steps are involved: The alloy powder is sequentially subjected to pretreatment, forming, sintering and heat treatment to obtain a product; The pretreatment process is as follows: in an air environment, heating the temperature to 200-300°C at a heating rate of 2-5°C / min, keeping the temperature for 1-2 hours, cooling the furnace to room temperature and then taking the furnace out; The heat treatment process is: in a vacuum environment with a vacuum degree of ≤0.01Pa, heating to 500-600°C at a heating rate of 5-10°C / min, keeping the temperature for 1-2h, then cooling in water or quenching oil to room temperature and taking out of the furnace.
4. The method for preparing a high coercive force soft magnetic alloy according to claim 3, characterized in that: The alloy powder is prepared by one of a gas atomization method, a water atomization method and a water-gas combined atomization method.
5. The method for preparing a high coercive force soft magnetic alloy according to claim 3, characterized in that: The average particle size of the alloy powder is 2-5 μm.
6. The method for preparing a high coercive force soft magnetic alloy according to claim 3, characterized in that: The forming is any one of compression molding and cold isostatic pressing; the forming pressure of the compression molding is 100-300MPa, and the holding time is 5-10min; the forming pressure of the cold isostatic pressing is 100-200MPa, and the holding time is 3-8min.
7. The method for preparing a high coercivity soft magnetic alloy according to claim 3, characterized in that: The sintering process is as follows: in a vacuum environment with a vacuum degree of ≤0.01 Pa, heating to 1200-1300° C. at a heating rate of 5-10° C. / min, keeping the temperature for 1-4 hours, cooling to room temperature and taking out of the furnace.
8. A high coercivity soft magnetic alloy and a preparation method thereof according to any one of claims 1 to 7, characterized in that: The coercive force of soft magnetic alloy is 20~30A / m.